1-methylcyclopropene effects on volatile profile and quality of 'Royal Gala' apples produced in Southern Brazil and stored in controlled atmosphere - Thewes,Fabio Rodrigo (2015)
ABSTRACT: Apple volatile aroma depends of complex interaction among organic compounds. The aim of the present study was to evaluate the effect of 1-methylcyclopropene (1-MCP) application on volatile profile and quality on 'Royal Gala' apples produced in Southern Brazil and stored under controlled atmosphere condition (CA; 1.0kPa O2+1.2kPa CO2; 0.5±0.1°C; 94±1% relative humidity). Volatile profile was determined after eight month of CA storage plus 7 days of shelf life via solid-phase microextraction (HS-SPME) and analyzed by gas chromatography coupled to mass spectrometer. In the volatile profile were identified 8 esters, 11 alcohols, 6 aldehydes, 6 acids, 2 ketones, 1 ether and 1 terpene. 1-MCP application reduced significantly the main volatile compounds production by 'Royal Gala' apples produced in Southern Brazil. Its application decreases significantly the esters production, especially 2-methyl-butyl acetate and hexyl acetate, compared to 'Royal Gala' apples storage under CA. 1-methylcyclopropene application decrease ethylene production and respiration rate. Apples treated with 1-MCP exhibit higher hexanal and 2(E)-hexenal production.